EPIDEMIOLOGICAL PROFILE OF ACQUIRED SYPHILIS IN THE NORTHERN REGION OF BRAZIL FROM 2011 AND 2021: Perfil epidemiológico da sífilis adquirida na região norte do Brasil de 2011 e 2021 - Silva Serrão, Fernanda; Silva, Mariana Simão Costa da; Soares Leite, Daniela (Revista de Ciências da Saúde Nova Esperança, 2024)
Sexually transmitted infections are among society’s most recurring public health dilemmas. Syphilis is an infectious, contagious disease exclusive to humans, transmitted through unprotected sexual contact. It is estimated that 11 million new cases of syphilis occur annually in adults aged 15 to 49 worldwide. The aim of this study was to identify the epidemiological profile of acquired syphilis in the states of the Northern region of Brazil between 2011 and 2021. This is an observational study with a quantitative, retrospective approach, using data from SINAN, available on DATASUS. Sociodemographic variables were analyzed: gender, age, race, level of education, and diagnosis criteria. It was found that between 2011 and 2021, 50,810 cases of acquired syphilis were reported in the states of the Northern region of Brazil. The state of Amazonas had the highest notification rate with 18,709 (36.82%) cases, followed by the state of Pará with 13,102 (25.79%) notifications and Tocantins with 6,728 (13.24%) notified cases. The year 2018 showed the highest incidence rate of the period, decreasing from 2019 onwards. Thus, the profile of acquired syphilis in the Northern region was: males, aged between 20 and 39, brown, with unknown schooling, and regarding the diagnostic criterion, laboratory diagnosis had the highest rate of notifications. This highlights the need to promote actions aimed at elucidating sexual health and offering effective measures to combat syphilis in the most affected population, as well as the need to re-evaluate the mandatory fields on the SINAN notification and investigation forms since they represent an essential source for determining health indicators.